The Role of Self‐Talk in Downgrading a Teacher's Certainty About Grammar Matters. Issue 1 (19th May 2020) - Hall, Joan Kelly; Looney, Stephen Daniel
Abstract : Second language (L2) teaching is complex interactional work. Although how teachers teach is known to be significant to student engagement and learning, the specialized nature of teaching is typically represented as knowledge and beliefs about teaching. This is changing, however, as the number of studies drawing on ethnomethodology and conversation analysis to illuminate the intricacies of L2 teaching is rapidly growing. This study adds to this research. Its specific focus is on an English as a second language teacher's use of self‐talk to downgrade her certainty about the appropriate use of particular linguistic constructions that are the focus of instruction. The authors argue that, rather than displaying ineptitude at these moments, the use of self‐talk displays the teacher's skilled willingness to make public her thinking processes as she works through her uncertainty and models for students ways they might deal with similar challenges. Shifting the focus to what teachers do, the study offers insight into the complex, embodied work of teaching, which, in turn, contributes to a practice‐based understanding of teaching. For both novice and experienced teachers, the instructive descriptions of teacher self‐talk can help them develop a reflective capacity for understanding and dealing with the contingencies of L2 teaching. Abstract :